'Renowned and unknown': Calouste Gulbenkian as collector of paintings. (13th October 2017) - Conlin, Jonathan
Abstract: Combining Impressionist, Barbizon and Dutch seventeenth-century masterpieces with eighteenth-century French and English portraits and Venetian veduti, the collection of paintings formed by the Anglo-Armenian financier and oil magnate Calouste Gulbenkian (1869–1955) and now housed in the Gulbenkian Museum, Lisbon closely resembles collections formed by contemporaries such as Henry Frick and Jacques Doucet. The manner of its acquisition, however – most notably purchases from Russia's Hermitage Museum – displayed a 'buccaneer' element. New research shows how Gulbenkian leveraged his oil interests as well as promises of a bequest to influence the leading British, French and American agents, dealers and curators of the twentieth century.